2017
DOI: 10.1080/01419870.2017.1392027
|View full text |Cite
|
Sign up to set email alerts
|

Is racism the new sectarianism? Negativity towards immigrants and ethnic minorities in Northern Ireland from 2004 to 2015

Abstract: Negativity towards ethnic minorities is a serious problem in Northern Ireland. Its history of the Troubles around religious identities makes Northern Ireland a special case in Europe. This paper examines negativity towards Muslims, Eastern Europeans and immigrants in Northern Ireland using data from the Northern Ireland Life and Times Survey and the British Social Attitudes Survey. The results from regressions show that anti-immigrant negativity is no more prevalent in Northern Ireland than elsewhere in the UK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…New immigrants to the island from Africa, Asia, the Middle East, and Eastern Europe have enriched both cultures as local people meet new ideas and new practices. However, in recent years racist hate crimes have increased against immigrants and ethnic minorities as the economy relapsed (Doebler et al 2017). Yet sectarianism lies deep within the society due to segregated communities, neighbourhoods as well as green and orange politics.…”
Section: Resultsmentioning
confidence: 99%
“…New immigrants to the island from Africa, Asia, the Middle East, and Eastern Europe have enriched both cultures as local people meet new ideas and new practices. However, in recent years racist hate crimes have increased against immigrants and ethnic minorities as the economy relapsed (Doebler et al 2017). Yet sectarianism lies deep within the society due to segregated communities, neighbourhoods as well as green and orange politics.…”
Section: Resultsmentioning
confidence: 99%
“…The Troubles certainly contributed to a society that had very limited ethnic diversity in the late 20 th century. However, the contemporary lack of ethnic diversity is perpetuated by an environment perceived as unwelcoming to outsiders (Doebler et al, 2017). Over the last two decades, Ulster Rugby has made a significant effort to broaden its player base beyond its traditional Protestant grammar-school foundation, and Ballycross RFC featured six players who identified as Catholic in 2015/16.…”
Section: Methodsmentioning
confidence: 99%
“…These sectarian and racist discourses intersect, and performances of one prejudice open the door for multiple expressions of prejudice. Doebler et al, (2017) found that the 'War on Terror', ISIS terror attacks and anti-Muslim discourses in the press have all contributed to increasing racism towards, and rejection of, Muslims as family members, with 18-24 year olds the most intolerant.…”
Section: White Others and Non-white Othersmentioning
confidence: 99%
“…First, the period of relative peace between the major paramilitary organizations in Northern Ireland has meant more people have chosen to settle in the territory. Second, demographic changes have arisen as a result of the EU expansion that allowed greater freedom of movement between Western Europe and the A8 accession countries (Doebler et al 2018). Following the GFA, and the expansion of EU membership to include the A8 members, there was a sustained period of significant inward migration into Northern Ireland, which tailed off following the financial crisis in 2008 (Russell, 2012;.…”
Section: An Increasingly Multicultural Northern Irelandmentioning
confidence: 99%